The characterization of large order (3, r)-regular graphs - Laffin M.R.; Özkan S. (Utilitas Mathematica, 2016)
In this paper, we sharpen the bound given by Jamison and Johnson in [4] on large order (t, r)-regular graphs for the case t = 3. We also determine all (3, r)-regular graphs for small values of r.